Formulation development, optimisation and in-vitro characterisation of a cubosomal gel loaded with metronidazole - Ndlovu, Handsome (Rhodes University, 2026)
Metronidazole (MTZ) is a synthetic nitroimidazole antibiotic with activity targeted against anaerobic bacteria and protozoa. MTZ is a prodrug and requires intracellular activation by reducing the nitro group to a nitroso-radical which reacts and forms covalent bonds with DNA of the offending organism, causing damage to the double helical structure of bacterial DNA and leading to inhibition of bacterial nucleic acid synthesis, eventually resulting in bacterial cell death. Most periodontal pathogens are Gram-negative bacteria and the administration of MTZ is a therapeutically justified intervention due to the established activity of MTZ against Gram-negative organisms. Most side effects of MTZ are tolerable. The bitter and metallic taste of MTZ remains a challenge to address as it directly affects patient adherence and therapeutic outcomes. Formulation development and optimisation of a cubosomal gel loaded with MTZ were conducted to deliver MTZ locally at the periodontal pocket while minimizing systemic and local side effects and the development of bacterial resistance due to large doses of antibiotics given to manage periodontitis. Before formulation studies were conducted, a reverse phase high performance liquid chromatography with an ultra-violet detector (RP-HPLC-UV) was successfully developed, optimised and validated using ICH guidelines and it was rapid, precise, accurate, specific and stability indicating and was used to analyse MTZ in pharmaceutical dosage forms including the cubosomal gel that was formulated. Preformulation studies were conducted with the aim of selecting the excipients for a stable cubosomal formulation. No physical and, or chemical interactions were found between MTZ and selected excipients. MTZ maintained its crystallinity form in all analyses. The poor solubility of MTZ in glyceryl monooleate necessitated the inclusion of co-surfactant polyvinyl alcohol in addition to Pluronic F127 as a surfactant. For all cubosomal formulations conducted, top-down approach was adapted. The developed formulation was optimised using Version 12.0.1.0 Design Expert® statistical software (Stat-Ease Inc., Minneapolis, MN, USA). Fisher’s test for Analysis of Variance (ANOVA) was used to establish model adequacy. Four formulation variables were considered for Box-Behnken design (BBD) viz glyceryl monooleate (GMO), oleic acid (OA), Pluronic® F-127 (F-127) and polyvinyl alcohol (PVA) on their influence on critical quality attributes (CQA) viz. entrapment efficiency (EE), particle size (PS), Zeta potential (ZP) and poly-dispersity index (PDI). The BBD optimised formulation was further optimised using Doehlert design (D-optimal) were the influence of process parameters viz. sonication time and frequency were investigated on the CQA. The final optimised formulation had an EE of 38.71%, PS of 34.30 nm, ZP of -26.6 mV and PDI of 0.152. Characterisation of the optimized formulation involved assessing loading capacity, which was found to be 1.74% and was attributed to low EE of MTZ in cubosomes. In-vitro drug release studies showed a burst release with about 14% of MTZ released within five minutes. Sustained release was observed after three hours of dissolution testing. In-vitro release kinetics followed Higuchi and Korsemeyer-Peppas models with R2 values of 0.9924 and 0.9493, respectively. The value of n was 0.3661 (n < 0.5), which indicated a diffusion-controlled release mechanism, Quasi-Fickian diffusion. FTIR showed no new functional group stretches and the main MTZ characteristic peaks were observed in the cubosomal formulation. The evaluation of taste using an electronic tongue (E-tongue) revealed that cubosomes had successfully masked the bitter taste of MTZ as the PCA biplots showed a clear distance between pure MTZ solution and cubosomal formulations. Short term (22 ºC/60±5% RH) and accelerated stability (40 ºC/75%RH) studies conducted for 4 weeks revealed that CQA for the optimised formulations decreased with time with a significant decrease being observed for 40 ºC/75%RH. A colour change from white translucent gel to light brown colour was observed for formulations kept at 40 ºC/75%RH. Despite decrease in CQA except for EE, the CQA parameters remained within acceptable limits for a cubosomal formulation as the PS was still between 10-500 nm, PDI < 0.3 and ZP > ±15 mV. Storage in the locker at 22 ºC showed no observable change in terms of colour and presence of visible particulate matter. The formulations were comparable to the freshly prepared cubosomal formulation. The stability studies gave an indication that room temperature (22 ºC) may be appropriate as storage conditions although long term stability studies are recommended.
Keywords: Uncatalogued